2007
DOI: 10.1038/modpathol.3800902
|View full text |Cite
|
Sign up to set email alerts
|

Solid pseudopapillary neoplasms of the pancreas show an interruption of the Wnt-signaling pathway and express gene products of 11q

Abstract: Solid pseudopapillary neoplasms of the pancreas almost consistently show a b-catenin mutation activating the Wnt-signaling pathway, resulting in overexpression of cyclin D1, but not in overt malignancy of this tumor. Besides cyclin D1, a set of markers (ie FLI-1, CD56 and progesterone receptor), whose genes map to chromosome 11q, are frequently expressed in solid pseudopapillary neoplasms. Chromosome 11q is a region that is also often affected in pancreatic neuroendocrine tumors. This immunohistochemical study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 27 publications
(29 reference statements)
7
46
0
3
Order By: Relevance
“…14 Subsequent papers showed that although FLI-1 is overexpressed in solid pseudopapillary neoplasms, 17 it is more likely due to a genetic alteration involving the long arm of chromosome 11 rather than an EWS-FLI-1 transcript. 20 Interestingly, two of our patients showed loss of 11q22.3, and one showed a gain at 11q13.5-q14, suggesting a role for changes in chromosome 11q during the development of solid pseudopapillary neoplasms.…”
Section: Discussionmentioning
confidence: 60%
“…14 Subsequent papers showed that although FLI-1 is overexpressed in solid pseudopapillary neoplasms, 17 it is more likely due to a genetic alteration involving the long arm of chromosome 11 rather than an EWS-FLI-1 transcript. 20 Interestingly, two of our patients showed loss of 11q22.3, and one showed a gain at 11q13.5-q14, suggesting a role for changes in chromosome 11q during the development of solid pseudopapillary neoplasms.…”
Section: Discussionmentioning
confidence: 60%
“…Recent studies have also highlighted the genetic and immunophenotypic expression patterns of b-catenin and E-cadherin in SPN and PEN. [29][30][31] In conclusion, we wish to highlight that large, clear cytoplasmic vacuoles can serve as a critical clue with which to distinguish SPN from PEN in diagnostically challenging cases. In such cases, adequate samples should be obtained to perform supportive ancillary studies as needed.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of protein products of chromosome 11q genes, such as cyclin D1, CD56, and FLI-1, is also characteristic [ 44 ]. Allelic loss on chromosome 5q22.1 was frequently found by Min Kim et al [ 42 ].…”
Section: Molecular Diagnostic Features and Cytogeneticsmentioning
confidence: 99%